Large‐scale evaluation of SLC18A2 in prostate cancer reveals diagnostic and prognostic biomarker potential at three molecular levels. Issue 6 (9th February 2016) - Haldrup, Christa; Lynnerup, Anne-Sofie; Storebjerg, Tine Maj; Vang, Søren; Wild, Peter; Visakorpi, Tapio; Arsov, Christian; Schulz, Wolfgang A.; Lindberg, Johan; Grönberg, Henrik; Egevad, Lars; Borre, Michael; et al.
Abstract : Limitations of current diagnostic and prognostic tools for prostate cancer (PC) have led to over‐diagnosis and over‐treatment. Here, we investigate the biomarker potential of the SLC18A2 (VMAT2) gene for PC at three molecular levels. Thus, SLC18A2 promoter methylation was analyzed in 767 malignant and 78 benign radical prostatectomy (RP) samples using methylation‐specific qPCR and Illumina 450K methylation microarray data. SLC18A2 transcript levels were assessed in 412 malignant and 45 benign RP samples using RNAseq data. SLC18A2 protein was evaluated by immunohistochemistry in 502 malignant and 305 benign RP samples. Cancer‐specificity of molecular changes was tested using Mann–Whitney U tests and/or receiver operating characteristic (ROC) analyses. Log rank, uni‐ and multivariate Cox regression tests were used for survival analyses. We found that SLC18A2 promoter hypermethylation was highly cancer‐specific (area under the curve (AUC): 0.923–0.976) and associated with biochemical recurrence (BCR) after RP in univariate analyses. SLC18A2 transcript levels were reduced in PC and had independent prognostic value for BCR after RP (multivariate HR 0.13, P < 0.05). Likewise, SLC18A2 protein was down‐regulated in PC (AUC 0.898) and had independent prognostic value for BCR (multivariate HR 0.51, P < 0.05). Reduced SLC18A2 protein expression was also associated with poor overall survival in univariate analysis (HR 0.29, P < 0.05). Our results highlight SLC18A2 as a new promising methylation marker candidate for PC diagnosis. Furthermore, SLC18A2 expression (RNA and protein) showed promising prognostic potential beyond routine clinicopathological variables. Thus, novel SLC18A2‐based molecular tests could have useful future applications for PC detection and identification of high‐risk patients. Highlights: The SLC18A2 gene is hypermethylated and downregulated in prostate cancer (PC). SLC18A2 hypermethylation has promising diagnostic biomarker potential for PC. Loss of SLC18A2 (protein/RNA) is an independent adverse predictor of PSA recurrence. Loss of SLC18A2 protein in PC is associated with poor survival after prostatectomy. SLC18A2 protein/RNA‐based future prognostic tests may help identify high‐risk PC.